Asking for help: An empirical exploration into social grammar - Andreas Trotzke; Attila Balla; Hannah Grobauer; Eva Wittenberg (PLoS ONE, 2025)
This paper explores the interface between linguistic form and social meaning by focusing on correlations between sentence type and the social distance between interlocutors—a central aspect of the social meaning component of politeness. We present a forced-choice experiment with four different groups of speakers (L1 British English speakers, L1 American English speakers, L2 English/German speakers, and L1 German speakers). In this experiment, we manipulated the linguistic form of asking for help along the syntactic dimension of sentence type (declaratives, interrogatives, or imperatives) and recorded the addressee our participants picked for each form (brother, coworker, or stranger). We broaden the empirical picture by going beyond highly conventionalized forms (e.g., Can you VP?) and therefore also varying the modal auxiliary verbs (e.g., Will you VP?). Based on this comprehensive picture of ways of asking for help, we identify clusters of linguistic forms depending on their felicity in different social scenarios. Our descriptive cluster analysis as well as the statistical comparisons between sentence types indicate that there are systematic correspondences between linguistic form and social meaning across different groups of speakers and languages, and we propose that our empirical data provide a potential starting point for rethinking speech act grammar in terms of ‘social grammar’.